Better Cotton: An Approach to Sustainable Agriculture - Noor Nabi Bhutto; Absar Mithal Jiskani; Ghulam Mustafa Nizamani (Journal of Applied Agricultural Science and Technology, 2022)
Cotton is the largest industrial sector in Pakistan. However, due to bad traditional practices and use of high amount pesticides, the whole industry lost about 10-15% of cotton. For reasons of socioeconomic and environmental harm, the Better Cotton Initiative (BCI) launched "Better Cotton" in Pakistan. Better cotton production is a more environmentally friendly alternative to traditional cotton due to its efficient resource utilization and lower environmental externalities. CABI encourages farmers to implement better cotton production principles and criteria, use better cotton standard system and good agricultural practices (GAP), and provide participatory training for small, medium and large-sized farmers and farm workers in their "learning groups" and medium-sized farmers' fields. The aim of this short communication article is to put together a concise review of Better Cotton production. In this short communication we briefly present the history, importance, aim, distribution and principles of Better Cotton Initiative.